Memaknai Ulang Film Ajari Aku Islam Perspektif Roland Barthes - heryanti; Jamaluddin Arsyad; Ahdiyat Mahendra (Journal of Religion and Film, 2022)
This research is motivated by the rapid development of information and communication technology. One of them is the development of film. In the course of its history this film has become a very large and profitable industry. Film is a form of mass media that can spread messages with its technical advantages. This study aims to describe the representation of the moral message in the film Ajari Aku Islam in terms of denotation, connotation and myth. and knowing the religious values​​contained in the film Teach Me Islam by jaymes Rianto. This study uses interpretive qualitative research. This approach allows the author to make in-depth observations and analyzes of the object to be studied. In the process the researcher will direct interactive qualitative research to explain moral values ​​seen through the meanings of denotations, connotations, and myths and representations contained in the film Ajari Aku Islam with the Roland Barthes model. This research seeks to describe facts that are interpreted correctly. As a result, the writer finds that the scene contains several meanings and messages, namely: the moral message of the importance of tolerance in religion; Then the religious messages contained in certain parts of the dialogue. Namely the values ​​of the aqidah which discuss faith in Allah SWT, the moral values​​include the morals towards oneself, parents, family and society, the values ​​of worship include prayer. Recommendation, For Muslims, tolerance and mutual respect for differences can help us to build friendship in a society that has diversity in terms of culture, ethnicity, and ethnicity.